2016
DOI: 10.18844/gjgc.v6i2.1211
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and life satisfaction as the predictors of general self-efficacy

Abstract: The purpose of this study is to determine whether there is a relationship among general self-efficacy, resilience, life satisfaction and the extent to which the variables of resilience and life satisfaction contribute to the prediction of general self-efficacy. The study was carried out with 310 middle-aged adults in Burdur, 195 (62.9%) of which were female, 115 (37.1&) were male, 70 (22.6%) were single, 227 (73.2%) were married and 13 (4.2%) were divorced. The General Self-Efficacy Scale, the Resilience i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…Higher levels of SE were associated with higher levels of LS. These results are coherent with a body of research that has linked SE with other well-being outcomes (Tagay, Karatas, Bayar, & Savi-Cakar, 2016;Marcionetti & Rossier, 2016;Masaud Ansari, & Khan, 2015;Wright, & Perrone, 2010). Regression analyzes showed that, both ignorance and exclusion by peers, predicted LS negatively.…”
Section: Discussionsupporting
confidence: 87%
“…Higher levels of SE were associated with higher levels of LS. These results are coherent with a body of research that has linked SE with other well-being outcomes (Tagay, Karatas, Bayar, & Savi-Cakar, 2016;Marcionetti & Rossier, 2016;Masaud Ansari, & Khan, 2015;Wright, & Perrone, 2010). Regression analyzes showed that, both ignorance and exclusion by peers, predicted LS negatively.…”
Section: Discussionsupporting
confidence: 87%
“…Especially the inquiries related to religious beliefs and spirituality had the lowest loadings, which may be a reason for eliminating the questions with the weakest loadings [63]. Also, the factors of spiritual In previous studies, such as [71,72] and based on the results of this study, it is a positive correlation between CD -RISC and general self-e cacy. It is expected that an increase in resilience level will lead to an increase in general self-e cacy levels as adolescents with self-e cacy levels are more successful in di cult situations [72].…”
Section: Discussionmentioning
confidence: 80%
“…PPC also increases faster and creates individuals with higher life satisfaction. PPC has been more closely linked to life satisfaction [55]. These prior studies suggest a correlation between PPC and satisfaction.…”
Section: Positive Psychological Capital and The Life Satisfaction Of ...mentioning
confidence: 90%